Emergency Department Use Among Hispanic Adults: The Role of Acculturation - Allen, Lindsay (Med Care, 2016)
OBJECTIVES: We provide the first known examination of differences in non-urgent and urgent emergency department usage between Hispanic and non-Hispanic white individuals, with varying levels of acculturation. METHODS: We pooled cross-sectional data for Hispanic and non-Hispanic white adults (ages 18–64) from the 2011–2013 National Health Interview Surveys. Using logistic regression models, we examined differences in past-year emergency department use, urgent emergency department use, and non-urgent emergency department use by acculturation level, which we measure by combining information on respondents’ citizenship status, birthplace, and length of stay (immigrants <5 , 5–10, >10 years in US; naturalized citizens; US-born). RESULTS: Overall, 17.8% of Hispanic individuals and 18.5% of non-Hispanic white individuals use the emergency department annually. Compared to U.S.-born non-Hispanic white individuals, the least acculturated Hispanic individuals are 14.4 percentage points (p<0.001) less likely to use the emergency department for any reason, 9.8 percentage points (p<0.001) less likely to use it for a non-urgent reason, and 5.3 percentage points (p<0.01) less likely to use it for an urgent reason. CONCLUSIONS: Contrary to popular perception, the least acculturated Hispanic individuals are the least likely to use the emergency department. As acculturation level rises, so does one’s likelihood of using the emergency department, particularly for non-urgent visits.